2022
DOI: 10.1128/msystems.00352-22
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mechanisms Shaping the Plastisphere Microbiota in Soil

Abstract: The increasing pervasive microplastic pollution is creating a new environmental compartment, termed plastisphere. Even though there was conclusive information characterizing the plastisphere, the underlying mechanisms shaping the bacterial communities in the plastisphere in the soil remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…We utilized only a limited number of soils and microplastics. The highly diverse soils and microplastics may induce great variance in observations. , Furthermore, the priming effect (PE), referring to the change in the decomposition rate of native SOM after fresh organic matter input, induced by microplastics was not investigated. Microplastics may exhibit a negative PE via sorbing soil DOM on particle surfaces to decrease the decomposition of native SOM or leaching easily mineralized organic carbon to induce the preferential metabolization of exogenous carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized only a limited number of soils and microplastics. The highly diverse soils and microplastics may induce great variance in observations. , Furthermore, the priming effect (PE), referring to the change in the decomposition rate of native SOM after fresh organic matter input, induced by microplastics was not investigated. Microplastics may exhibit a negative PE via sorbing soil DOM on particle surfaces to decrease the decomposition of native SOM or leaching easily mineralized organic carbon to induce the preferential metabolization of exogenous carbon.…”
Section: Resultsmentioning
confidence: 99%
“…First, changes in the soil microbial community were not included. Previous studies indicated that microplastics could change the community compositions, , which may potentially impact the soil carbon stability. We utilized only a limited number of soils and microplastics.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether and how different exogenous additives affect the stability of the bacterial co-occurrence network, a robustness analysis was performed to evaluate the stability of networks and their embedded members ( Yuan et al., 2021 ; Sun et al., 2022 ). Robustness refers to the stability of the structure and function of a biological system when it is disturbed by uncertain factors.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial responses toward plastic and plastic carbon in anoxic blue carbon sediments may clarify many uncertainties related to microbial growth, extracellular polymeric substances, and carbon mineralization. Research related to the “plastisphere” community (i.e., the microbial community on plastic surfaces) in various environmental compartments, especially in surface waters and surface sediments, has advanced in recent decades. However, information regarding microbial metabolism on plastic buried in blue carbon sediment remains insufficient (Panel ).…”
Section: How Can Plastic Carbon Affect Blue Carbon?mentioning
confidence: 99%